Tenofovir disoproxil fumarate-associated hypophosphatemia as determined by fractional excretion of filtered phosphate in HIV-infected patients. Issue 11 (November 2016) - Cheng, Chien-Yu; Chang, Shu-Yin; Lin, Mei-Hui; Ku, Shin-Yen; Sun, Na-Lee; Cheng, Shu-Hsing
Abstract: Introduction: Tenofovir disoproxil fumarate (TDF) -containing regimens have been associated with nephrotoxicity and hypophosphatemia in HIV-infected patients. The objective of this study was to assess the possible risk factors for hypophosphatemia and evaluate the relationship between fractional excretion of filtered phosphate (FePi) and hypophosphatemia in TDF users. Patient and methods: Patients were enrolled in a prospective cohort study between January 2011 and December 2014. We classified experienced HIV-infected patients (individuals maintained on antiretroviral therapy (ART) for 6 months or more) and naïve patients into 3 treatment groups: TDF-containing ART (group 1), non-TDF-containing ART (never received TDF or had not received TDF in the past 6 months; group 2) and naive to antiretroviral therapy (group 3). Specimens from each individual were assessed for serum phosphate, serum creatinine, urine phosphate, and urine creatinine. Multivariable logistic regression was performed to control for the following variables measured at baseline: eGFR, age, sex, sexual orientation, injection drug use (IDUs), HIV-RNA viral load, and CD4 cell count. Results: The frequency of hypophosphatemia in groups 1, 2, and 3 was 20.2%, 7.2%, and 14.6%, respectively ( P  = 0.002). FePi above 10% also was significantly associated with hypophosphatemia ( P  = 0.003; adjusted odds ratio = 2.54). Patients with elevated CD4 cell counts (>500 cells/μL) exhibited a lower risk of hypophosphatemia ( P  = 0.002; adjusted odds ratio = 0.35). Conclusions: Hypophosphatemia is a multifactorial etiology; FePi was confirmed as a suggested method to predict the risk of hypophosphatemia in TDF users. Clinical Trial Number: TYGH103011.